Obama and research in human embryonic stem cells - Arias Stella, Javier (2009)
The most recent and astonishing scientific advances have allowed the development of fertilization techniques based on the somatic cell nuclear transfer method. Thanks to this, it has been possible to widen knowledge about embryo cells, maintaining their pluripotentiality and now there are some cell banks available for therapeutic purposes.However, embryo cell manipulation has been the subject of many discussion from the scientific, ethics, and politics point of view, because of many fears generated by the likelihood of manipulating the genetic machinery of a non-differentiated totipotent stem cell.In the last Presidential Elections in the USA, Mr. Barack Obama proimised to strengthen research in this promising field. This promise opens the way for many patients that are awaiing for therapy options that nowadays still are not possible.